Sengketa Wanprestasi Perjanjian Perusahaan Patungan Dengan Pihak Investor Asing Berdasarkan Pilihan Hukum dan Pilihan Forum - Sihombing, Sony Putri Lestari; Yudhantaka, Lintang (Legal Spirit, 2025)
One form of investment cooperation carried out in Indonesia to help improve the Indonesian economy is Joint Venture cooperation. A joint venture is a business carried out jointly between foreign investors (PMA) and domestic investors (PMDN) based on an agreement or known as a joint venture agreement which is the basis for forming a new legal entity. The thesis with the title Legal Protection of Investors for Disputes of Default on Joint Venture Agreements Based on Law Number 25 of 2007 concerning Capital Investment is normative research where the background to the problem when in practice joint venture cooperation does not always comply with what is stated in the Joint Venture agreement. Things like this are what give rise to joint venture cooperation disputes between investment parties. This research uses normative law (normative law research) which can be concluded as the act of studying various kinds of formal legal rules such as laws and the type of approach in this research uses a statutory approach (statue approach). The results of this research indicate that incoming foreign investors must establish a limited liability company in the form of a joint venture collaboration based on the Investment Law, this is to provide legal certainty for the parties. The existence of these legal regulations ensures that capital investment, which is the scope of the implementation of the national economy, can be positioned as an effort to increase economic growth. During the period of cooperation, it is possible that disputes will arise between the parties. It is hoped that the investment parties will be able to choose and take into account what legal remedies are best for resolving the disputes that occur. Every party involved in drafting the substantive contents of the agreement must be careful considering that the joint venture agreement will be the basis and guideline for the parties to carry out the operations of the Joint Venture company.